An agent-based Decision Support System for resources' scheduling in Emergency Supply Chains. (February 2017) - Ben Othman, Sarah; Zgaya, Hayfa; Dotoli, Mariagrazia; Hammadi, Slim
Abstract: We propose a multi-agent-based architecture for the management of Emergency Supply Chains (ESCs), in which each zone is controlled by an agent. A Decision Support System (DSS) states and solves, in a distributed way, the scheduling problem for the delivery of resources from the ESC supplying zones to the ESC crisis-affected areas. Thanks to the agents' cooperation, the DSS provides a scheduling plan that guarantees an effective response to emergencies. The approach is applied to two real cases: the Mali and the Japan crisis. Simulations are based on real data that have been validated by a team of logisticians from Airbus Defense and Space.